2016
DOI: 10.1590/0037-8682-0270-2015
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus-positive gastric cancer: a distinct molecular subtype of the disease?

Abstract: Approximately 90% of the world population is infected by Epstein-Barr virus (EBV). Usually, it infects B lymphocytes, predisposing them to malignant transformation. Infection of epithelial cells occurs rarely, and it is estimated that about to 10% of gastric cancer patients harbor EBV in their malignant cells. Given that gastric cancer is the third leading cause of cancerrelated mortality worldwide, with a global annual incidence of over 950,000 cases, EBV-positive gastric cancer is the largest group of EBV-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 55 publications
2
23
0
3
Order By: Relevance
“…Another international pooled analysis included 4,599 GC patients from 13 studies and found that tumor EBV positivity was 8.2% . Compared to EBV‐negative gastric carcinoma (EBVnGC), EBV associated gastric carcinomas (EBVaGCs) reportedly affects younger males, is of the preferential Lauren diffuse subtype, and its predominance is in the proximal and remnant stomach . Most studies showed a favorable survival for the EBVaGC patients, although some study reported no relationship between EBV infection and survival or even worse .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another international pooled analysis included 4,599 GC patients from 13 studies and found that tumor EBV positivity was 8.2% . Compared to EBV‐negative gastric carcinoma (EBVnGC), EBV associated gastric carcinomas (EBVaGCs) reportedly affects younger males, is of the preferential Lauren diffuse subtype, and its predominance is in the proximal and remnant stomach . Most studies showed a favorable survival for the EBVaGC patients, although some study reported no relationship between EBV infection and survival or even worse .…”
Section: Introductionmentioning
confidence: 99%
“…5 Compared to EBV-negative gastric carcinoma (EBVnGC), EBV associated gastric carcinomas (EBVaGCs) reportedly affects younger males, is of the preferential Lauren diffuse subtype, and its predominance is in the proximal and remnant stomach. 4,[6][7][8][9] Most studies showed a favorable survival for the EBVaGC patients, 5,[10][11][12] although some study reported no relationship between EBV infection and survival or even worse. 13,14 EBVaGC are generally defined by the presence of EBV in gastric carcinoma cells by in situ hybridization (ISH) targeting EBV-encoded RNA (EBER).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that 8% to 10% GC were associated with EBV infection. 20 The Cancer Genome Atlas project also revealed that amplification of JAK2, CD274 (also known as PD-L1) and PDCD1LG2 (also known as PD-L2) was frequently observed in EBVpositive gastric adenocarcinoma. 19 However, in our patient, EBV was absence in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, more than 950,000 cases of gastric adenocarcinoma are diagnosed in the world annually and the relationship between this type of cancer and EBV is estimated to be around 10%. A meta-analysis comprising 9,738 cases evaluated the frequency of EBV-associated gastric cancer (EBVaGC) at the level of 8.8% [4]. Every year, EBVaGC Increasing interest has been focused on the Epstein-Barr Virus (EBV)-associated cancers, including oropharyngeal cancer (OPC) and gastric cancer (GC).…”
Section: Introductionmentioning
confidence: 99%